PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Gazali Gazali; Ummi Wahyuni (Al-Amien Prenduan for Islamic Institute, 2021)
The results of the company's work will depend on the results of the performance of its employees. The company will try to improve the performance of its employees by encouraging its employees to work optimally with one way, namely the provision of compensation. This is in accordance with the theory which says that satisfaction with compensation can affect employee behavior to work more enthusiastically and spur high performance. This research is classified as explanatory research with a quantitative approach. The sample used was 64 respondents with saturated sampling technique. The type of data used is primary data, namely collecting data using a questionnaire. The data analysis used is Multiple Linear Regression with SPSS version 21 tool. The results of this study indicate that compensation is able to have a positive impact on employee performance, with a significance value of 0.000 which means below 0.05 and has a positive coefficient value of 0.698. Job satisfaction is able to have a positive impact on employee performance, with a significance value of 0.000 which means below 0.05 and has a positive coefficient value of 0.522. Compensation is able to have a positive impact on job satisfaction, with a significance value of 0.000 which means below 0.05 and has a positive coefficient value of 1.334. and Compensation has a positive effect on employee performance with Job Satisfaction as an intervening variable, with a significance value of 0.000 which means below 0.05 and has a calculated F value of 5486.521 which means above F table is 2.36.